Adjuvant pembrolizumab versus placebo in resected stage III melanoma (EORTC 1325-MG/KEYNOTE-054): distant metastasis-free survival results from a double-blind, randomised, controlled, phase 3 trial. Issue 5 (May 2021) - Eggermont, Alexander M M; Blank, Christian U; Mandalà, Mario; Long, Georgina V; Atkinson, Victoria G; Dalle, Stéphane; Haydon, Andrew M; Meshcheryakov, Andrey; Khattak, Adnan; Carlino, Matteo S; Sandhu, Shahneen; Larkin, James; et al.
Summary: Background: The European Organisation for Research and Treatment of Cancer (EORTC) 1325/KEYNOTE-054 trial assessed pembrolizumab versus placebo in patients with resected high-risk stage III melanoma. At 15-month median follow-up, pembrolizumab improved recurrence-free survival (hazard ratio [HR] 0·57 [98·4% CI 0·43–0·74], p<0·0001) compared with placebo, leading to its approval in the USA and Europe. This report provides the final results for the secondary efficacy endpoint, distant metastasis-free survival and an update of the recurrence-free survival results. Methods: This double-blind, randomised, controlled, phase 3 trial was done at 123 academic centres and community hospitals across 23 countries. Patients aged 18 years or older with complete resection of cutaneous melanoma metastatic to lymph node, classified as American Joint Committee on Cancer staging system, seventh edition (AJCC-7) stage IIIA (at least one lymph node metastasis >1 mm), IIIB, or IIIC (without in-transit metastasis), and with an Eastern Cooperative Oncology Group performance status of 0 or 1 were eligible. Patients were randomly assigned (1:1) via a central interactive voice response system to receive intravenous pembrolizumab 200 mg or placebo every 3 weeks for up to 18 doses or until disease recurrence or unacceptable toxicity. Randomisation was stratified according to disease stage and region, using a minimisation technique, and clinical investigators, patients, and those collecting or analysing the data were masked to treatment assignment. The two coprimary endpoints were recurrence-free survival in the intention-to-treat (ITT) population and in patients with PD-L1-positive tumours. The secondary endpoint reported here was distant metastasis-free survival in the ITT and PD-L1-positive populations. This study is registered with ClinicalTrials.gov, NCT02362594, and EudraCT, 2014-004944-37. Findings: Between Aug 26, 2015, and Nov 14, 2016, 1019 patients were assigned to receive either pembrolizumab (n=514) or placebo (n=505). At an overall median follow-up of 42·3 months (IQR 40·5–45·9), 3·5-year distant metastasis-free survival was higher in the pembrolizumab group than in the placebo group in the ITT population (65·3% [95% CI 60·9–69·5] in the pembrolizumab group vs 49·4% [44·8–53·8] in the placebo group; HR 0·60 [95% CI 0·49–0·73]; p<0·0001). In the 853 patients with PD-L1-positive tumours, 3·5-year distant metastasis-free survival was 66·7% (95% CI 61·8–71·2) in the pembrolizumab group and 51·6% (46·6–56·4) in the placebo group (HR 0·61 [95% CI 0·49–0·76]; p<0·0001). Recurrence-free survival remained longer in the pembrolizumab group 59·8% (95% CI 55·3–64·1) than the placebo group 41·4% (37·0–45·8) at this 3·5-year follow-up in the ITT population (HR 0·59 [95% CI 0·49–0·70]) and in those with PD-L1-positive tumours 61·4% (56·3–66·1) in the pembrolizumab group and 44·1% (39·2–48·8) in the placebo group (HR 0·59 [95% CI 0·49–0·73]). Interpretation: Pembrolizumab adjuvant therapy provided a significant and clinically meaningful improvement in distant metastasis-free survival at a 3·5-year median follow-up, which was consistent with the improvement in recurrence-free survival. Therefore, the results of this trial support the indication to use adjuvant pembrolizumab therapy in patients with resected high risk stage III cutaneous melanoma. Funding: Merck Sharp & Dohme.